Sustainable food consumption in Portugal: examining the enablers and barriers towards the consumption of pulses - Botelho, Catarina Alexandra Luz (2021)
The sustainability of the food systems depends greatly on the gradual transition from animal to plant-based proteins. However, some plant-based proteins, like pulses, continue to be under valued. This study aims to examine there as on behind the low consumption of pulses in Portugal, by understanding the relationship between the barriers and enablers towards its consumption, mapped according to Capability, Opportunity, and Motivation, and the(1) consumers’ choice of pulses in different real-life scenarios, (2) consumers’ intake of pulses in a regular week, and(3)consumers’ intention to consume pulses more often. An online questionnaire, that included a dish-composition experience, direct questions, and open questions, was distributed, and 398 valid answers were obtained. The results revealed that both Capability and Motivation seem to positively impact the frequency of choice of pulses in almost all the different scenarios and in a regular week. Moreover, results revealed that Capability, Opportunity, and Motivation were positively correlated with the consumers’ intention to consume pulses more often. This study could serve as guidance for businesses that intend to reduce the existent barriers and develop strategies to increase the consumption of pulses in Portugal.